The Phenomenon Šiltāqāt And Its Reflections In The Armenian Historical Milieu - Margaryan, Gor («Քոփի Փրինթ» տպ.)
Since the end of the XIV century, in official documents and written sources on the history of the Ilkhanate, the term šiltāqāt is often found, the meaning of which is still not fully understood. The interpretation of the term was often given without regard to the substantive characteristics of the word: šiltāqāt is interpreted partially, sometimes conflicting, and approximately meaningful comments are given. Šiltāqāt has been interpreted as an illegal tax, a tax levied under various pretexts, a pretext or extraordinary tax, generally as a collective name for lawless taxes, etc. Moreover, what was the meaning and application of šiltāqāt? If it was a tax, in what amount, where, how, and under what circumstances was it levied? Surely, since the Ilkhanid period šiltāqāt was levied on the subject peoples, and hence the term should have been reflected in the reports of the economic life of those same peoples. In particular, the article deals with the mention of šiltāqāt in the Armenian sources, the use and semantic meanings of the term or phenomenon. Interestingly, during the post-Ilkhanid period until the early 16th century, the term does not occur in Armenian sources at all. However, later on, begining from the 16th century in Armenian historical sources, and interestingly, also in various Armenian dialects, the term (sometimes in a distorted form) is often found, as well as a description of the phenomenon. The purpose of this article is to collect all the information and references to šiltāqāt in the Armenian sources, and on the basis of this as additional historical material, try to make clarifications of šiltāqāt, its application, meaning, etc. by means of source analysis. Հոդվածում փորձ է կատարվել ներկայացնել որպես հարկային եզրույթ, չարաշահում, ապօրինի հարկահանություն, տուգանք և տարբեր այլ նշանակություններով հայտնի շիլթաղաթ երևույթի՝ հայկական ուշմիջնադարյան իրականության արտահայտումներն ու կիրառության դեպքերը, ընկալումներն ու դրա վերաբերյալ մեկնաբանությունները: Բացի այդ քննվում է հայկական աղբյուրներում և բարբառներում տեղ գտած եզրույթի նշանակությունը, հայտվելու պատճառներն ու ժամանակաշրջանը և նրան հարիր իմաստային նրբերանգները:
Keywords: Etymology; Armenian sources